2017
DOI: 10.1038/s41566-017-0054-7
|View full text |Cite
|
Sign up to set email alerts
|

Broadband gate-tunable terahertz plasmons in graphene heterostructures

Abstract: Graphene, a unique two-dimensional material of carbon in a honeycomb lattice [1], has brought remarkable breakthroughs across the domains of electronics, mechanics, and thermal transport, driven by the quasiparticle Dirac fermions obeying a linear dispersion [2-3]. Here we demonstrate a counter-pumped all-optical difference frequency process to coherently generate and control THz plasmons in atomic layer graphene with an octave tunability and high efficiency. We leverage the inherent surface asymmetry of graph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
113
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(114 citation statements)
references
References 30 publications
0
113
0
1
Order By: Relevance
“…We thus expect the EQ-type responses of graphene to have an even higher efficiency in the infrared frequency range. All these may explain the strong surface plasmon enhanced difference-frequency generation observed by Constant et al [32] and Yao et al [33].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…We thus expect the EQ-type responses of graphene to have an even higher efficiency in the infrared frequency range. All these may explain the strong surface plasmon enhanced difference-frequency generation observed by Constant et al [32] and Yao et al [33].…”
Section: Introductionmentioning
confidence: 78%
“…The electron-hole symmetry operator is , which gives , | ⟩ | ̅ ⟩, and . We then have: 33 ( ) ( ), which leads to:…”
Section: B) the Electron-hole Symmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2015, Springer Nature. f) Gate tunability of the DFG graphene plasmons with V g increase from –0.2 to 0.2 V. Reproduced with permission . Copyright 2017, Springer Nature.…”
Section: Far‐field Optical Methodsmentioning
confidence: 99%
“…Constant et al excited graphene plasmons with a defined wavevector and direction across a large frequency range (up to tens of THz) by controlling the phase matching conditions (Figure e). Yao et al demonstrated THz graphene plasmons are generated and controllable with a counter‐pumped all‐optical DFG (Figure f). In addition, Yao et al showed DFG is also suitable for generating surface plasmons in Bi 2 Se 3 (a type of TIs), which has the same massless Dirac fermions feature as graphene.…”
Section: Far‐field Optical Methodsmentioning
confidence: 99%